PENGARUH KOMBINASI KONSENTRASI PUPUK ORGANIK CAIR (SUPER FARM) DAN KULTIVAR TERHADAP PERTUMBUHAN DAN HASIL PAKCOY (Brassica rapa L.) - Achmad Faqih; Nunnik Ameyliska (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2017)
The purpose of this experiment the effect of liquid was to organic fertilizer (Super Farm) and cultivars on growth and yield pakcoy (Brassica rapa L.). The experiment was conducted in UPTD BPBP Plumbon Cirebon. The location is above 17 m a thigh of sea level, with soil type is regosol. The time of research was conducted on June until July.The experiments used was experimental method Randomized Design (RBD) consists of two factors and repeated three times. The first factor of the liquid organic fertilizer concentration levels: control (without POC), 1 ml/l of water, 2 ml/l of water, 3 ml/l of water, 4 ml/l of water, 5 ml/l of water. The second factor consists of two cultivars cultivar that is green and green pakcoy putsoi. The variables measured were plant height, number of leaves, plants per plot gross weight, net weight of plants per plot, gross weight per plant, and gross weight per plant.Concentration combination treatment of liquid organic fertilizer (Super Farm) and cultivars provide significant effect on the average variable plant height, number of leaves per plant, gross weight per plant, planting net weight, gross weight per plot, and the net weight per plot. Concentration combination treatment of liquid organic fertilizer (Super Farm) 2.0 ml/l of water on the cultivar Green Pakcoy and Green Putsoi can provide the best results in the net weight per plot of 8.764 kg/plot and 8.803 kg/plot, equivalent to 35.056 tons/ha and 35.212 tons/ha.